ANALISIS GOOD CORPORATE GOVERNANCE, LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL PEMODERASI - Zaenal Muttaqin; Atika Fitriyani; Taridi Kasbi Ridho; Deni Pandu Nugraha (Tirtayasa Ekonomika, 2019)
The purpose of this study was to determine the effect of good corporate governance and leverage on firm value with profitability as moderating variable. The sample in this study is the company of the Consumer Goods sector that is listed on the Indonesia Stock Exchange. The company samples that were successfully obtained and fulfilled the criteria were as many as 28 companies, where the research was carried out for 5 years since 2013-2017. The analysis technique used Moderated Regression Analysis (MRA). The results showed that, (1) Good corporate governance represented by audit committees and independent comissioner, had a positive effect on firm value, (2) Leverage represented by DAR, negatively not affected firm value, (3) Profitability represented by ROA, had a positive effect on firm value, (4) Good corporate governance represented by audit committees and moderated by profitability proves that profitability is able to moderate GCG and has a positive effect on company value, (5) leverage represented by DAR and moderated by profitability proves that profitability is not able to moderate leverage and negative effect on company value.